Studi*Eksperimental Karakteristik Dan Regenerasi Kalsium Klorida Sebagai Material Pada Pengkondisian Udara Adsorpsi - Yuhna, Cut Tasya; Sucipta, Made; Negara, D N K Putra (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstract To get a sense of comfort in a room, an air conditioning or (AC) system is used by using a compressor and requires large amounts of electrical energy, thus increasing the number of global warming and the energy crisis. Referring to this, an environmentally friendly and energy efficient cooling system is needed. The alternative is to use calcium chloride material in adsorption air conditioning. In this system, changes in temperature and humidity levels are obtained from the process of absorption of water vapor in the air that occurs in calcium chloride material in the packed bed. The purpose of this study was to analyze the characteristics of CaCl2 and its performance against humidity. The characteristics tested also include the contact angle test. The results obtained, the performance of CaCl2 is very good in reducing the absolute humidity of the air in the test chamber (dehumidification). This can also be seen from the addition of water vapor mass in CaCl2, but it has little effect on the decrease in room temperature. It's just that the regeneration of CaCl2 is not good because the CaCl2 material tends to change phase. Keywords: Adsorption air conditioning, calcium chloride, characteristics, regeneration, and humidty